2019
DOI: 10.1080/02626667.2019.1639716
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow prediction in ungauged basins: analysis of regionalization methods in a hydrologically heterogeneous region of Mexico

Abstract: Streamflow prediction in ungauged basins: analysis of regionalization methods in a hydrologically heterogeneous region of Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Yang, Magnusson, Rizzi, et al (2018) made a comprehensive assessment of the regionalization methods in the high latitudes of Norway and found that distance‐based similarity approaches (spatial proximity, physical similarity) performed better than regression‐based approaches. Arsenault, Breton‐Dufour, Poulin, Dallaire, and Romero‐Lopez (2019) also evaluated three regionalization methods in Mexico and discovered that the donor‐based spatial‐proximity regionalization method was to be preferred in semi‐arid and humid ungauged catchments. These results agree with previous conclusions.…”
Section: Hydrological Regionalization Methodsmentioning
confidence: 99%
“…Yang, Magnusson, Rizzi, et al (2018) made a comprehensive assessment of the regionalization methods in the high latitudes of Norway and found that distance‐based similarity approaches (spatial proximity, physical similarity) performed better than regression‐based approaches. Arsenault, Breton‐Dufour, Poulin, Dallaire, and Romero‐Lopez (2019) also evaluated three regionalization methods in Mexico and discovered that the donor‐based spatial‐proximity regionalization method was to be preferred in semi‐arid and humid ungauged catchments. These results agree with previous conclusions.…”
Section: Hydrological Regionalization Methodsmentioning
confidence: 99%
“…Finally, land cover www.nature.com/scientificdata www.nature.com/scientificdata/ fractions are also as expected, with large portions of the United States Midwest having cropland as the dominant land use category and major forested areas in Canada, north-east United States and Western United States. Figure 5 also shows that the Mexican catchments are highly heterogeneous in terms of physiographic attributes 40 .…”
Section: Technical Validationmentioning
confidence: 99%
“…The popular regionalization methods are physical similarity, spatial proximity, and regression 5 . Previously, many studies have been conducted and compared the performance of the regionalization methods to predict total streamflow or direct runoff 6 in the ungauged catchment with various hydrological models (WASMOD 7 , VIC 8 , SWAT 9 , GR4J 10 , HMETS 10 , MOHYSE 10 , and HEC-HMS 11 ) for different regions. Some of them showed that distance-based (spatial proximity, physical similarity) outperformed regression methods 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Swain and Patra 3 pointed that the spatial proximity between the gauged catchment and the ungauged catchment gave better results than the physical similarity for predicting the continuous streamflow. Arsenault et al 10 studied the efficacy of three regionalization methods: multiple linear regression (MLR), spatial proximity, and physical similarity, to predict current flow in ungauged catchments of Mexico. They showed that transferring a set of parameters from a nearby reservoir is the most efficient method for estimating the runoff in ungauged basins.…”
Section: Introductionmentioning
confidence: 99%